Predictors of adverse course of severe communityacquired pneumonia associated with coronavirus infection - Avgaitis, S. S. (My University, 2024)
The global COVID-19 pandemic caused by SARS-CoV-2 has spread from the epidemic centre in Wuhan, China to countries around the world. Unfortunately, the impact of the COVID-19 pneumonia outbreak and the ultimate scope of the pandemic remain unclear.